Production of camu camu plants with different organic substrates in conventional nursery bed - Abanto Rodriguez, Carlos (2013)
The aim was to verify the initial development of camu camu plants with different organic substrates in conventional nursery bedding microsprinkler irrigation and shade management Chromatine® mesh with 50% red light. We used genetic material from mother plants Germplasm Bank of INIA-camu camu Iquitos, seeds were germinated in decomposed sawdust and kept for a period of 40 days after subculturing was performed with 10 cm in height in different substrates according treatments in nursery beds with dimensions of 1.20 m wide x 10 m long with a depth of 30 cm. After conducting assessments of height (cm) and basal diameter (mm) for a period of 120 days, it was found that the substrate manure has become the substrate for greater efficiency in plant development camu camu substrate followed by humus worm.